The Metropolitan affair - Green, Jocelyn (Green, Jocelyn. On Central Park, 2023)
"With a notorious forger preying on New York's high society, Metropolitan Museum of Art curator Lauren Westlake is just the expert needed to track down the criminal. As she and Detective Joe Caravello search for the truth, the closer they get to discovering the forger's identity, the more entangled they become in a web of deception and crime"--